The impact of crisis and macroeconomic variables towards Islamic banking deposits - Abduh, Muhamad; Omar, Mohd. Azmi; Duasa, Jarita (Science Publications, 2011)
Problem statement: The nature of Islamic banks is different from conventional banks which may lead to a different deposit behavior of their depositors. This study aims to analyze the dynamic effects of interest and profit rate changes, production level, inflation and financial crisis towards the fluctuation of total deposits in Malaysian Islamic banks. Approach: Using monthly data from January 2000 to December 2010, cointegration test and vector error correction model were utilized to uncover the dynamic relationship between macroeconomic variables and crisis with total deposit of Islamic banking. Results: The results show that changes in interest and profit rate as well as production growth has no significant effects. Meanwhile, inflation has negative effect on total deposits of Islamic banks which reflects the changes on depositors’ consumption pattern during the recession.Interestingly, financial crisis is positively affecting total deposits in Islamic banks. Conclusion: This study provides evidence of general consumer sentiment and deposit behavior. It indicates that in general,due to the 1997/1998 financial crisis experience, bank depositors have trusted Islamic banking to be more resilient in facing financial crisis and hence, inflow of deposits to Islamic banks was happened during 2007/2008 financial crisis